BnALMT7-A4 encodes an aluminium-activated malate transporter that enhances aluminium tolerance in both Brassica napus L. and Arabidopsis thaliana - Cao, Xulyu; Liu, Aihui; Zhang, Xiaoyong; Liu, Kaiyang; Ren, Lanyang; Liu, Can; Coates, Juliet C.; Li, Nannan (Frontiers in Plant Science, 2026)
IntroductionAluminium (Al) toxicity in acidic soil is a key limiting factor of agricultural productivity and sustainability. ALUMINIUM-ACTIVATED MALATE TRANSPORT (ALMT) homologs regulate responses to acidic soil conditions by releasing malate to chelate toxic Al3+ ions, thus also reducing the ability of Al3+ to bind to inorganic phosphate (Pi) and lower Pi bioavailability. In rapeseed (Brassica napus), BnALMT1 and BnALMT2 mitigate Al stress. However, function of BnALMT7, in the same clade as BnALMT1, remains unknown. Here we identified and characterised ALMT7 homologs (BnALMT7-A4 and BnALMT7-C4) in rapeseed, and used one homolog, BnALMT7-A4, to engineer both Al-tolerant Arabidopsis plants and Al-tolerant Brassica hairy roots, and to understand the mechanism by which this Al-tolerance is conferred by BnALMT7-A4.MethodsBnALMT7-A4 and BnALMT7-C4 gene expression was characterised using qRT-PCR and promoter activity was assayed with a pBnALMT7-A4::GUS fusion. The protein structres were assessed by modelling and BnALMT7-A4 was characterised using a BnALMT7-A4-GFP fusion protein and a split luciferase assay. Transgenic Arabidopsis and rapeseed hairy root lines overexpressing BnALMT7-A4 were generated to investigate the function of BnALMT7-A4 under Al stress, including via transcriptomic analysis.ResultsBnALMT7-A4 and BnALMT7-C4 were predicted to be transmembrane proteins. BnALMT7-A4 showed the greatest similarity to Arabidopsis AtALMT7, localised to the plasma membrane and formed homodimers. In addition to their constitutive expression in flowers and siliques, both BnALMT7-A4 and BnALMT7-C4 were significantly induced by Al treatment in roots. The promoter of BnALMT7-A4 was specifically active in the root vascular system. Phenotypic analysis of overexpression lines generated in both Arabidopsis plants and Brassica hairy roots revealed that BnALMT7-A4 promoted root growth, with less Al accumulation occurring in the root tips of transgenic plants. Transcriptomic analysis showed that overexpression of BnALMT7-A4 resulted in upregulation of genes response to oxidative stress and downregulation of genes involved in detoxification in the presence of Al.DiscussionWe have identified a putative aluminium-activated malate transporter, BnALMT7-A4, that is induced by Al treatment in roots. We engineered Arabidopsis and Brassica overexpressing BnALMT7-A4 to generate Al-tolerant plants with improved root growth and reduced Al accumulation in root tips. Transcriptomic analysis of the Al-tolerant Brassica roots demonstrated modification of stress- and toxicity-specific gene expression. Thus, we have discovered a new way of making rapeseed, an important crop, more tolerant to Al stress.